Response of planktonic foraminifera to seasonal and interannual hydrographic changes: Sediment trap record from the northern South China Sea - Lin, Hui-Ling; Lui, Hon-Kit; Lin, Tai-Chun; Wang, You-Lin (Frontiers in Earth Science, 2022)
Foraminifera play an important role in the organic and inorganic carbon pumps of the ocean. Understanding their responses in seasonal and interannual time scales to the climate and seawater chemistry changes is important in studying carbon cycles and paleoclimatology. This study examined about 5.1-year continuous mass fluxes in 2013/9–2019/8 and 1.8-year planktonic foraminiferal time series in 2016/8–2019/8 census from ten and four sets of sediment trap, respectively, moored at the South East Asia Time-series Study (SEATS) site in the northern South China Sea (SCS), the world’s largest marginal sea. A total of four sets of sediment trap mooring with 11 common species identified, spanning from August 2016 to August 2019 with 8-day and 16-day collecting periods, provided access to evaluate the impact of the prevailing monsoon system and interannual climatic conditions. Our results show that the winter monsoon enhances the nutrient inventories in the euphotic zone, supporting the productivity and the mass and shell fluxes. In addition to seasonal cycles, the variation of chlorophyll-a concentration in the SCS shows a strong response to wind speed under the influence of El Niño–Southern Oscillation (ENSO). The reduction in wind speed and the intensification of Kuroshio intrusion during the ENSO warm phases reduces the productivity, mass, and shell fluxes, and vice versa in the case of the ENSO cold phases. The imprint of an ENSO cold phase (La Niña event) in 2017 was signified by 2–3-fold higher values than the 3-year average of total mass and foraminiferal shell fluxes. Instead of the common dominance of Trilobatus sacculifer and Globigerinoides ruber among species composition, Neogloboquadrina dutertrei was the predominant species comprising over 40–60% of total shells greater than 212 μm. Furthermore, the interval with an elevated abundance of N. dutertrei lasted throughout January 2018 (four collecting intervals). Foraminifera shell fluxes were the lowest during warm months (March–August) in 2019, which was coeval with the increase in proportions of Orbulina universa and Globigerinella calida. The unusual species composition might signify a weak ENSO warm phase (a weak El Niño event) between September 2018 and August 2019.